2007
DOI: 10.1111/j.1532-5415.2007.01448.x
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Banxia Houpu Tang, a Traditional Chinese Medicine, for Reducing Pneumonia Risk in Older Adults with Dementia

Abstract: Treatment with BHT reduced the risk of pneumonia and pneumonia-related mortality in elderly patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 22 publications
0
33
1
1
Order By: Relevance
“…In a previous observer-blinded, randomized, controlled trial, a significantly reduced aspiration pneumonia risk was observed after Ban-Xia-Hou-Po-Tangs (Pinellia and Officinal Magnolia Bark Decoction) treatment, with an adjusted hazard ratio slightly lower than that in the present study; [28] Ma-Xing-Gan-Shi-Tang (Ephedra, Apricot Kernel, Licorice, and Gypsum Decoction) was reported to relieve the symptoms of chronic bronchitis [29] and lower respiratory tract infection. [30] It was indicated to protect influenza virus infection through inhibiting both viral RNA and protein synthesis, [31] and could reduce lung inflammation and inhibit virus replication in mice infected with respiratory syncytial virus.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In a previous observer-blinded, randomized, controlled trial, a significantly reduced aspiration pneumonia risk was observed after Ban-Xia-Hou-Po-Tangs (Pinellia and Officinal Magnolia Bark Decoction) treatment, with an adjusted hazard ratio slightly lower than that in the present study; [28] Ma-Xing-Gan-Shi-Tang (Ephedra, Apricot Kernel, Licorice, and Gypsum Decoction) was reported to relieve the symptoms of chronic bronchitis [29] and lower respiratory tract infection. [30] It was indicated to protect influenza virus infection through inhibiting both viral RNA and protein synthesis, [31] and could reduce lung inflammation and inhibit virus replication in mice infected with respiratory syncytial virus.…”
Section: Discussioncontrasting
confidence: 58%
“…[3] Further, vaccination, [4] correct posture, [5] and swallowing rehabilitation [6] have also been suggested to reduce the incidence of pneumonia. In addition, a prospective, observer-blinded, randomized controlled trial revealed Ban-Xia-Houpu-Tang (HangeKobokuTo in Japanese, English Name: Pinellia and Officinal Magnolia Bark Decoction) can reduce the incidence of aspiration pneumonia, [7] and follow-up studies confirmed it might improve the swallowing reflex in patients with dementia. [8] Further, an observational study found combined using traditional and western medicine might decrease the hospital stay length, body temperature, and white blood cell count compared with western medicine treatment only.…”
Section: Introductionmentioning
confidence: 99%
“…Although Chinese herbs have been reported to reduce pneumonia risk in elderly patients with dementia [27] and regarded as a potential treatment of Huntington's disease (HD) [28], the attempts to apply this alternative treatment in SCA are still few. Okabe et al (2007) reported a patient with SCA6 was treated with a mixture of 18 medical herbs (modified Zhengan Xifeng Tang) and then the patient's ataxia was remarkably reduced [29].…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening research of the pathological mechanism of PD, more and more Chinese and foreign scholars are concerned about a lot of Chinese medicine and its monomer composition in the mechanism of PD [10,11] …”
mentioning
confidence: 99%